(untitled) (CIPEEX, 2022)
IMMEDIATE MODERNITY IS €ŒLIQUID€ AND €ŒFAST€, MORE DYNAMIC THAN THE €ŒSOLID€ MODERNITY IT HAS SUPPLANTED. THE CONCEPT OF LIQUID MODERNITY WAS DEVELOPED BY THE POLISH SOCIOLOGIST ZYGMUNT BAUMAN AND REFERS TO A NEW ERA IN WHICH SOCIAL, ECONOMIC AND PRODUCTION RELATIONS ARE MALLEABLE, LIKE LIQUIDS. IN THE MIDST OF THIS CONSUMERIST SOCIETY AND VOLATILE DESIRES, THE CONCEPT OF ECOLOGICAL SUBJECT DEVELOPED BY ISABEL CRISTINA DE MOURA CARVALHO EMERGES, A WAY OF BEING RELATED TO THE ADOPTION OF A LIFESTYLE ECOLOGICALLY ORIENTED BY ECOLOGICAL VALUES. THE PRESENT WORK ARISES FROM THE NEED TO INVESTIGATE AND ANALYZE THE INTERRELATIONSHIPS AND COMPLEXITIES OF THE CONCEPTS OF LIQUID MODERNITY AND ECOLOGICAL SUBJECT, AS WELL AS TO IDENTIFY WHAT CONTRIBUTIONS ENVIRONMENTAL EDUCATION AS A GUIDING THREAD CAN OFFER TO THE SEARCH FOR THE BALANCE OF THE RELATIONSHIP BETWEEN SOCIETY, CONSUMPTION AND ENVIRONMENT IN THE FORMATION OF THIS ECOLOGICAL SUBJECT. IT IS DIVIDED INTO THREE POINTS, INITIALLY DEALING WITH THE QUESTION OF THE CONCEPTION OF MODERNITY AND CONSUMPTION FROM THE IDEA OF €‹€‹ZIGMUND BAUMAN’S LIQUID SOCIETY. NEXT, THE THEME OF THE FORMATION OF THE ECOLOGICAL SUBJECT IS ANALYZED, ESTABLISHING ITS CONCEPTS AND IMPLICATIONS. FINALLY, IT WILL BE VERIFIED THAT ENVIRONMENTAL EDUCATION IS A TOOL OF CONTEMPORANEITY FOR THE SEARCH FOR BALANCE IN THE RELATIONS OF CONSUMPTION AND SUSTAINABILITY. WE PROPOSE THE ANALYSIS OF THE INTERFACE SOCIETY-NATURE AND ENVIRONMENTAL EDUCATION SUSTAINABILITY WITH A FOCUS ON THE POLITICAL PEDAGOGICAL PROJECTS OF THE MIDDLE LEVEL SCHOOLS OF THE REGIONAL EDUCATION OF ITAPACI-GO. THE METHODOLOGY OF THIS WORK MAKES USE OF BIBLIOGRAPHIC RESEARCH FOR A DESCRIPTIVE STUDY, CRITICAL OF THE CONTRIBUTIONS OF THESE AUTHORS, WITH QUALITATIVE RESEARCH AND MONOGRAPHIC WRITING.